Digital Media and Its Implication in Promoting Students’ Autonomous Learning - Wiwin, Darwin; Utami, Utami Widiati; Taris, Tarisman (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
Computer and internet technology encourage learners' autonomy by allowing them to choose the time, place, and circumstances conducive to learning (Ayllon et al., 2019; Baseghi, 2018; Rohatgi et al., 2016). The application of digital technology has meaningful connections with developing students' learning autonomy and promoting their skills independently. This research aimed to present meaningful information for the readers about the effectiveness of digital technology in promoting students' autonomous learning by answering the two research questions; what kinds of digital technology's characteristics, and which digital technology condition effectively promotes students' autonomous learning. The Systematical Literature Review includes seven articles selected from 19 articles in Google scholar, 1.215 articles in Science direct, and four articles in Sinta (1, 2, 3, 4, 5, and 6). The reviewed articles indicated seven apps; Schoology, Multimedia-assisted Instruction (MAI), Information Communication Technologies (ICTs), Memrises, Quizlet, Socrative, Sli-do, and Three-Dimensional (3D). The virtual environments allow students to promote their autonomous learning in such conditions as long-distance learning, classroom learning activities, and self-training activities.